Ultrasensitive and Broad‐Spectrum Photodetectors Based on InSe/ReS2 Heterostructure. Issue 5 (29th December 2021) - Ma, Haixin; Xing, Yanhui; Han, Jun; Cui, Boyao; Lei, Ting; Tu, Huayao; Guan, Baolu; Zeng, Zhongming; Zhang, Baoshun; Lv, Weiming
Abstract: Photogating effect based on vertical structure of 2D materials allows for the realization of a highly sensitive photodetector. A highly sensitive and broad‐spectrum (365–965 nm) photodetector is reported based on the indium selenide (InSe)/rhenium disulfide (ReS2 ) vertical heterostructure, where the top layer InSe serves as the photogate to regulate the channel current, enabling a large photoconductive gain of 10 6 . The detectivity of the photodetector can reach 6.51 × 10 13 Jones, making this one of the highest values among reported transition metal dichalcogenide photodetectors. The photodetector represents a high responsivity of 1921 A W −1, an ultrahigh external quantum efficiency (EQE) of 6.53 × 10 5 %, and a fast response time of 21.6 ms. The outstanding properties of the InSe/ReS2 heterojunction reveal the promising potential in high‐efficient, ultrasensitive, broadband photodetectors. Abstract : Nowadays, photodetectors are needed to meet the multiwavelength and high‐sensitivity detection requirements in complex application systems. A highly sensitive and broad‐spectrum photodetector based on the InSe/ReS2 vertical heterostructure is reported, in which ReS2 acts as the transport layer and the top layer InSe serves as the photogate to regulate the channel current.